Distribution of conjugated linoleic acid (CLA) isomers and other fatty acids in polar and neutral fractions of milk from cows fed different lipid supplements (2012)
ABSTRACT: milk fatty acid composition has become very important for consumers due to the positive relationship that has been found between some fatty acids and human health. In recent years, content and fatty acid composition in the different fractions of milk lipids has also become important due to reported potential technological and sensory implications. Objective: the aim of this study was to evaluate the effect of dietary supplementation with several lipid supplements on the proportion of neutral (triglycerides) and polar lipids (phospholipids) of milk fat, alterations of the fatty acid composition and Conjugated Linolenic Acid isomers (CLA) of total milk lipids. Methods: 18 first lactation German Holstein cows were assigned to three dietary treatments for 10 weeks as follows: Rumen-stable fractionated palm fat, linseed oil plus algae, and sunflower oil plus algae. Results: dietary polyunsaturated fat supplements increased the proportion of phospholipids and decreased triglycerides in milk fat compared to Rumen-stable fractionated palm fat. Long chain polyunsaturated fatty acids were preferentially deposited into phospholipids. Diet effect was more pronounced in triglycerides than in phospholipids. Plant oil/algae supplemented diets induced lower proportions of total saturated fatty acids and higher proportions of total unsaturated fatty acids in triglycerides. Conclusions: linseed oil plus algae feeding generated the best results in reference to fatty acids related to human health. Sunflower oil plus algae caused accumulation of CLAtrans-10,cis-12, CLAtrans-7,cis-9, CLAtrans-7,trans-9 and CLAtrans-10,trans-12 and decrease of CLAtrans-9,trans-11 in total milk fat, whereas linseed oil plus algae increased CLAtrans-12,trans-14, CLAtrans-11,trans-13, and CLAtrans-11,cis-13 deposition compared to rumen-stable fractionated palm fat.